PROBLEMS IN ASSESSING EPISTEMIC AUTHORITY OF UNIVERSITY PROFESSORS - Blumberga, Solveiga; Vorobjovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The authors provides reasons for the significance of assessment of epistemic authority of university professors, explicates the concept of epistemic authority and the issues related to research into this concept. In English, epistemic or epistemological means “of, relating to, or involving knowledge; cognitive”. An epistemic authority is a source of information who has a determining role in the process knowledge formation (Kruglanski, 1989). Authors analysed conceptual approaches to problems related to assessment of epistemic authority of university professors and to expand on the explanations to the problems in view of the results of the research study on student-perceived epistemic authority of university professors. The article includes the results of students (N=152) and graduates (N=210) of institutions of higher education located in Riga (Latvia).